2019
DOI: 10.1101/2019.12.19.882126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of a 6-week core exercises on swimming performance of national level swimmers

Abstract: 23 The aim of this study was to assess the impact of a 6-week specialized training program aimed at 24 strengthening core muscles to improve the effectiveness of selected elements of a swimming race in 25 group of elite polish swimmers. Sixteen male national and international level swimmers (21.6 ± 2.2 26 years) participated in the research. The competitors were randomly assigned to 1 of 2 groups before 27 the data collection process: an experimental (EG, n = 8) and control (CG, n = 8) group. Both groups 28 of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(47 reference statements)
1
0
0
Order By: Relevance
“…Although the method used in the literature shows similarity, the results obtained support this research [23]. In his study, Bıyıklı stated that core training, which was arranged in accordance with the age group before or during puberty, positively contributed to the physical performance of female swimmers in the 11-swimmers with mean 20.2 ± 1.17 age, it was found that it can be said that this core training affects the efficiency on a short distance of swimming performance (p<0.05) [24].…”
Section: Discussionsupporting
confidence: 74%
“…Although the method used in the literature shows similarity, the results obtained support this research [23]. In his study, Bıyıklı stated that core training, which was arranged in accordance with the age group before or during puberty, positively contributed to the physical performance of female swimmers in the 11-swimmers with mean 20.2 ± 1.17 age, it was found that it can be said that this core training affects the efficiency on a short distance of swimming performance (p<0.05) [24].…”
Section: Discussionsupporting
confidence: 74%